Immunization of mice against blood-stage Plasmodium yoelii malaria with isoelectrically focused antigens and correlation of immunity with T-cell priming in vivo. - De Souza, J B (1988)
Mice were immunized with lethal Plasmodium yoelii blood-stage malaria antigens that had been fractionated by isoelectric focusing using a variety of Ampholines over the range pH 3 to 10. Fractions were tested for their ability to protect against live challenge and to prime for parasite-specific T-cell help. Both activities exhibited three major peaks in the pH regions 4.5, 6.5, and 8, the pH 4.5 peak being the most consistently protective. There was a significant correlation between protection and T-helper-cell priming, particularly with antigens from the first peak, suggesting that T-cell priming represents an important component of the function of some protective malaria vaccines.